Arabic Language Learning as Economic Capital in the Hajj and Umrah Service Sector - Moh. Supriyadi (International Conference on Islamic Economic (ICIE), 2025)
Arabic language learning holds a strategic value in enhancing the communicative, social, and economic competencies of Muslim communities, particularly in the Hajj and Umrah service sectors. Arabic functions not only as a means of understanding Islamic teachings but also as economic capital that contributes directly to improving the welfare and professionalism of Muslim workers. In the context of globalized religious economics, proficiency in Arabic becomes a highly valuable functional skill that opens employment opportunities in religious service sectors such as pilgrimage assistance, religious tourism, education, and translation. This is increasingly relevant as the demand for professional personnel capable of effectively communicating with pilgrims and Saudi Arabian authorities continues to grow each year. This study employs a descriptive-analytical approach by examining various sources that discuss the interrelationship between language, economy, and religion. The results indicate that Arabic proficiency provides significant economic advantages, particularly for individuals working as guides, mutawwifs, translators, and other Hajj and Umrah service personnel. Beyond financial benefits, Arabic proficiency strengthens professional identity and improves the quality of pilgrim services. Moreover, need-based Arabic learning  has proven to be more effective in preparing a workforce that meets the real demands of the religious service industry. This research offers a new perspective on the urgency of need-based Arabic language learning as a strategy for human resource development that is more relevant to the dynamics of the Hajj and Umrah service industry. The findings are expected to serve as a reference for educational institutions, providers of religious professional training, and policymakers in designing Arabic language curricula and training programs that are more applicative, responsive, and aligned with the needs of the global job market.